Bioefficacy of Azoxystrobin 23% w/w SC Against Major Diseases of Sugarcane - Shailbala,; Kumar, Amarendra (International Journal of Bio-resource and Stress Management, 2023)
Sugarcane is severely affected by various diseases like red rot, smut, wilt, rust, leaf scald and yellow leaf that reduced the cane production in India. A field experiment was conducted to study the bio-efficacy of Azoxystrobin 23% w/w SC (Amistar 25 w/v SC) against sugarcane diseases during spring 2013–14 and 2014–15. The results revealed that among the various treatments, Azoxystrobin 23% w/w SC @ 1.00 ml l-1 showed 6.47 PDI and 6.15 PDI against red rot, 5.65 PDI and 5.12 PDI against rust, 6.25% and 5.66% disease incidence against smut and 4.95 and 4.23 PDI against wilt in 2013–14 and 2014–15 respectively. Treatments Azoxystrobin 23% w/w SC @ 1.00 ml l-1 and Azoxystrobin 23% w/w SC @ 1.25 ml l-1 was found significantly at par in controlling red rot, smut, wilt and rust disease of sugarcane. Treatment Azoxystrobin 23% w/w SC @ 1.25 ml lt-1 also recorded the significantly higher sugarcane yield of 749.60 q ha-1 and 768.95 q ha-1 which is significantly at par with Azoxystrobin 23% w/w SC @ 1.00 ml l-1 (741.17 q ha-1 and 759.92 q ha-1 respectively). It reduced disease significantly and thereby indirectly they reduced stress of pathogen on sugarcane crop. Yield increase in sprays could be attributed to the significant reduction of disease severity and thereby improvement of crop health for better growth and development. Hence, this fungicide at particular dose may also be viable alternatives for the management of sugarcane diseases.